8.

CotϴSecϴ = Cscϴ
CotϴSecϴ = (Cosϴ/Sinϴ)Secϴ
(Cosϴ/Sinϴ)Secϴ = (Cosϴ/Sinϴ)(1/ Cosϴ)
(Cosϴ/Sinϴ)(1/ Cosϴ)= 1/Sinϴ
1/Sinϴ= Cscϴ

[Cot=Cos/Sin]
[Sec=1/Cos]
[Cos factored out through multiplication)
[Definition of Csc]

9. (1-Sin²ϴ)(1+tan² ϴ)=1

12. Hi, since tan(x) = sin(x)/cos(x) and sec(x) = 1/cos(x) and since the expression can have meaning only if
sin(x) and cos(x) are not 0 you can write:
(sec(x) - cos(x))/tan(x) = (1/cos(x) - cos(x))/(sen(x)/cos(x)) =
= ((1 - cos^2(x))/cos(x))*(cos(x)/sen(x)) =
= (sen^2(x)/cos(x))*(cos(x)/sen(x)) = (sen(x)/cos(x))*cos(x) =
= tan(x)/(1/cos(x)) = tan(x)/sec(x).
13.

= (1+cos(x))/sin(x) + sin(x)/(1+cos(x))
= ((1+cos(x))² + sin²(x)) / (sin(x)(1+cos(x)))
= (1+2cos(x)+cos²(x)+sin²(x)) / (sin(x)(1 + cos(x))
= (2+2cos(x)) / (sin(x)(1+cos(x))
= 2(1+cos(x)) / (sin(x)(1+cos(x))
= 2/sin(x)
= 2csc(x)
14.
(1+s)/(1-s)-(1-s)/(1+s)
={(1+s)^2-(1-s)^2}/(1+s)(1-s)
={s^2+2s+1-s^2+2s-1}/(1-s^2)
=4s/c^2
=4tanx.(1/c)
=4tanx.secx

16.

(sinx+cosx)^2 =(sinx)^2 + (cosx)^2 + 2sinxcosx = 1 + sin2x

csc(2x)+cot(2x) = 1/sin2x + cos2x/sin2x =(1+cos2x)/sin2x = 2(cosx)^2/(2sinxcosx) = cosx/sinx = cotx 20. (s+c)(tanx+cotx) =(s+c)(s/c+c/s) =(s+c)((s^2+c^2)/sc) =(s+c)(1/sc). (s^2+c^2=1) =(s+c)/sc =1/c+1/s =secx +cosecx .

Sign up to vote on this title
UsefulNot useful